Genetic diversity of juçara palm: An alternative for selection and conservation in cash crop for fruit production - Mengarda, Liana Hilda Golin; Canal, Guilherme Bravim; Carvalho, Marina Santos; Ferreira, Adésio; Ferreira, Marcia Flores da Silva (Frontiers in Forests and Global Change, 2022)
The diversity of juçara palm (Euterpe edulis) must be investigated at the molecular level to enable the adoption of appropriate management strategies that may associate breeding studies with conservation. With the aim of to describe the genetic diversity and structure of a population of E. edulis in a managed area, the genotyping of 199 individuals was performed using nine microsatellite markers. We detected inbreeding in the population and the diversity within the plots was high showing diversity among the individuals. Two genetic groups were detected showing that individuals from the locality Santa Marta (plot 20) were divergent. The diversity indices observed in the studied area were close to those reported in the literature for natural populations; thus, the ex situ conservation of these individuals is feasible, as is their use in breeding studies.